Basic Vaccinations among Children Aged 12–23 Months in Northeast India: Trend, Pattern and Factors Influencing Low Coverage - Avijit Mistri; Soilalsiem Gangte (Indian Journal of Public Health)
India has experienced tremendous progress in childhood immunization through centralized flagship programs since 1985. There is a wide variation of immunization coverage of children aged 12–23 months among Indian states and regions. The North East (NE) region, including eight sister states, has witnessed low immunization coverage (68.4%) with higher dropouts (25%) and nonvaccinations (7.0%). NE Indian states substantially improved childhood immunization from 22.8% in 1992–93 to 68.4% in 2019–2021; still, it is below the national average (77%) and the lowest among the Indian States/UTs. Highly predictive determinants for the outcome of childhood vaccination status include maternal characteristics antenatal care for pregnancy, place of delivery, education level, and media exposure. A large section of the backward hilly tribes is also needed special attention to improving the levels of childhood vaccinations in NE states.